Higher-order Chromosome Structures Investigated by Polymer Physics in Cellular Morphogenesis and Differentiation. Issue 3 (7th February 2020) - Esposito, Andrea; Chiariello, Andrea M.; Conte, Mattia; Fiorillo, Luca; Musella, Francesco; Sciarretta, Renato; Bianco, Simona
Abstract: Experimental advances in Molecular Biology demonstrated that chromatin architecture and gene regulation are deeply related. Hi-C data, for instance, returned a scenario where chromosomes form a complex pattern of interactions, including TADs, metaTADs, and compartments, correlated with genomic and epigenomic features. Here, we discuss the emerging hierarchical organization of chromatin and show how it remains partially conserved during mouse neuronal differentiation with changes highly related to modifications in gene expression. In this scenario, models of polymer physics, such as the Strings & Binders (SBS) model, can be a crucial instrument to understand the molecular mechanisms underlying the formation of such a higher order 3D structure. In particular, we focus on the case study of the murine Pitx1 genomic region. At this locus, two alternative spatial conformations take place in the hindlimb and forelimb tissues, corresponding to two different transcriptional states of Pitx1 . We finally show how the structural variants can affect the locus 3D organization leading to ectopic gene expression and limb malformations. Graphical abstract: Image 1 Highlights: Novel technologies reveal the deep link between genome architecture and function. Chromosomes fold in a hierarchical structure of domains-within-domains. The String&Binders model successfully describes the genome folding mechanisms. Tissue-dependent architectures may promote or prevent specific regulatory contacts. Structural variants altering the chromatin structure can lead to gene mis-regulation.